Revisiting Pro Cultura Femminile’s Exhibitions on Domestic Culture (1932–1935) - Verhaeghe, Gerlinde (Lo sguardo rinnovato, 2026)
Founded in 1911, Turin’s emancipatory women’s organization Pro Cultura Femminile formulated its goal as “to do culture the feminine way”. To this end, Pro Cultura Femminile staged a series of exhibitions dedicated to female domestic culture. This chapter revisits two of these exhibitions: Mostra Femminile d’Arte Decorativa Moderna (1932) and L’Ora del The nella Casa Italiana (1935). Having taken place in the first half of the 1930s, the exhibitions testify to their changing societal, political, and cultural context. The chapter explores how the two exhibitions aim to make statements on domesticity from a female point of view, while increasingly becoming aligned with Fascist propaganda. It shows how women’s curatorial work engaged with and was shaped by the domestic ideology of Italian Fascism.